Radiological and Laboratory Features of Multiple Sclerosis Patients With Immunosuppressive Therapy: A Multicenter Retrospective Study in Japan - Ashida, Shinji; Ochi, Hirofumi; Hamatani, Mio; Fujii, Chihiro; Nishigori, Ryusei; Kawamura, Kazuyuki; Matsumoto, Sadayuki; Nakagawa, Masanori; Takahashi, Ryosuke; Mizuno, Toshiki; Kondo, Takayuki (Frontiers in Neurology, 2021)
Background: Multiple sclerosis (MS) is a relapsing, inflammatory, and demyelinating disease of central nervous system showing marked clinical heterogeneity. Many factors might influence the choice of relapse prevention drug, and treatment response varies among patients. Despite the enlargement of disease-modifying drugs for MS (MS-DMDs), some patients have been treated with corticosteroid and/or immunosuppressant (CS/IS). Objective: To clarify the radiological and laboratory features of MS treated with CS/IS for relapse prevention. Methods: Clinical records including radiological and laboratory findings, and drugs used for relapse prevention were reviewed retrospectively. Results: Out of 92 consecutive MS patients, 25 (27%) were treated with CS/IS. The followings were observed less frequently in patients treated with CS/IS than in those with MS-DMDs: 3 or more periventricular lesions, ovoid lesions, subcortical lesions, typical contrast-enhancing lesions, negative for serum autoantibodies, and positive for oligoclonal bands in the cerebrospinal fluid. Multiple logistic regression analysis revealed that the absence of typical contrast-enhancing lesions and positivity for serum autoantibodies were independent factors associated with CS/IS prescription (odds ratio 25.027 and 14.537, respectively). Conclusion: In this cohort of Japanese patients clinically diagnosed with MS, radiological and serological findings atypical of MS were observed more frequently in patients treated with CS/IS than in those with MS-DMDs as a part of MS therapy. The absence of contrast-enhancing lesions typical of MS and positivity for serum autoantibodies were independent factors strongly associated with CS/IS use.